Performance evaluation of single-phase induction motor controlled by variable frequency drive at non-ideal voltage conditions. Issue 2 (3rd April 2019) - Rahman, M. Ishtiaque; Salim, Khosru M.
ABSTRACT: This paper investigates the effects of low-voltage supply on single-phase irrigation systems by considering the case of Bangladesh Rural Electrification Board (BREB). Single-phase induction motors (SPIMs) are extensively employed in irrigation systems throughout the world. In Bangladesh, insufficient power generation and large transmission line impedances render the voltage at the consumer end much lower than expected from BREB. This reduces system efficiency and may even cause motor burnouts. Numerous control schemes for variable frequency drives have been published over the years. However, theoretical work regarding the performance analysis of single-phase VFDs under low-voltage conditions considering the mathematical model of the SPIM is rather scarce. In this paper, a modelled irrigation system containing a single-phase VFD is assessed in terms of key parameters such as operating voltage, frequency and efficiency. A system-specific relationship between the modulation index and output voltage of the single-phase VFD is achieved, and the effect of the volts-per-hertz control is illustrated. Finally, a comparison of the VFD-connected system with a conventional system without VFD is made using MATLAB Simulink. The results show that volts-per-hertz control significantly contributes in maintaining a decent efficiency throughout a wide voltage range, which is not the case for the conventional system.